The nature of chronic rejection after lung transplantation: a murine orthotopic lung transplant study - Heigl, Tobias; Kaes, Janne; Aelbrecht, Celine; Serré, Jef; Yamada, Yoshito; Geudens, Vincent; Van Herck, Anke; Vanstapel, Arno; Sacreas, Annelore; Ordies, Sofie; Frick, Anna; Saez Gimenez, Berta; et al. (Frontiers in Immunology, 2024)
Introduction Chronic rejection is a major complication post-transplantation. Within lung transplantation, chronic rejection was considered as airway centred. Chronic Lung Allograft Dysfunction (CLAD), defined to cover all late chronic complications, makes it more difficult to understand chronic rejection from an immunological perspective. This study investigated the true nature, timing and location of chronic rejection as a whole, within mouse lung transplantation. Methods 40 mice underwent an orthotopic left lung transplantation, were sacrificed at day 70 and evaluated by histology and in vivo µCT. For timing and location of rejection, extra grafts were sacrificed at day 7, 35, 56 and investigated by ex vivo µCT or single cell RNA (scRNA) profiling. Results Chronic rejection originated as innate inflammation around small arteries evolving toward adaptive organization with subsequent end-arterial fibrosis and obliterans. Subsequently, venous and pleural infiltration appeared, followed by airway related bronchiolar folding and rarely bronchiolitis obliterans was observed. Ex vivo µCT and scRNA profiling validated the time, location and sequence of events with endothelial destruction and activation as primary onset. Conclusion Against the current belief, chronic rejection in lung transplantation may start as an arterial response, followed by responses in venules, pleura, and, only in the late stage, bronchioles, as may be seen in some but not all patients with CLAD.